2020
DOI: 10.1128/jvi.00562-20
|View full text |Cite
|
Sign up to set email alerts
|

LY6E Restricts Entry of Human Coronaviruses, Including Currently Pandemic SARS-CoV-2

Abstract: C3A is a sub-clone of human hepatoblastoma HepG2 cell line with strong contact inhibition of growth. We fortuitously found that C3A was more susceptible to human coronavirus HCoV-OC43 infection than HepG2, which was attributed to the increased efficiency of virus entry into C3A cells. In an effort to search for the host cellular protein(s) mediating the differential susceptibility of the two cell lines to HCoV-OC43 infection, we found that ArfGAP with dual pleckstrin homology (PH) domains 2 (ADAP2), ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 80 publications
4
97
1
Order By: Relevance
“…The enhanced replication shown by SARS-CoV-2 with furin pre-cleaved spike to utilise TMPRSS2 to enter cells efficiently suggested this virus may prefer to enter cells via membranes near the cell surface or in the early endosome rather than be trafficked into late endosomes where it could be cleaved by host cathepsins. We hypothesised that the wild type virus may be avoiding host restriction factors in the endosome, such as IFITM2/3 proteins, which have previously been shown to be able to restrict SARS-CoV and SARS-CoV-2 entry (Huang et al, 2011; Zhao et al, 2020; Zheng et al, 2020). The antifungal agent amphotericin B (amphoB) has been well described as inhibiting the restriction imposed by IFITM proteins, particularly the endosomal/lysosomal localised IFITM2/3, potentially modulating the host membrane fluidity required for efficient restriction (Lin et al, 2013; Zhao et al, 2020; Zheng et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced replication shown by SARS-CoV-2 with furin pre-cleaved spike to utilise TMPRSS2 to enter cells efficiently suggested this virus may prefer to enter cells via membranes near the cell surface or in the early endosome rather than be trafficked into late endosomes where it could be cleaved by host cathepsins. We hypothesised that the wild type virus may be avoiding host restriction factors in the endosome, such as IFITM2/3 proteins, which have previously been shown to be able to restrict SARS-CoV and SARS-CoV-2 entry (Huang et al, 2011; Zhao et al, 2020; Zheng et al, 2020). The antifungal agent amphotericin B (amphoB) has been well described as inhibiting the restriction imposed by IFITM proteins, particularly the endosomal/lysosomal localised IFITM2/3, potentially modulating the host membrane fluidity required for efficient restriction (Lin et al, 2013; Zhao et al, 2020; Zheng et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesised that the wild type virus may be avoiding host restriction factors in the endosome, such as IFITM2/3 proteins, which have previously been shown to be able to restrict SARS-CoV and SARS-CoV-2 entry (Huang et al, 2011; Zhao et al, 2020; Zheng et al, 2020). The antifungal agent amphotericin B (amphoB) has been well described as inhibiting the restriction imposed by IFITM proteins, particularly the endosomal/lysosomal localised IFITM2/3, potentially modulating the host membrane fluidity required for efficient restriction (Lin et al, 2013; Zhao et al, 2020; Zheng et al, 2020). We could also show that 293T-ACE2, Caco-2, Calu-3 and HAEs all constitutively expressed IFITM3, even in the absence of exogenous interferon (Figure 3E-H).…”
Section: Resultsmentioning
confidence: 99%
“…IFITMs inhibit SARS-CoV, 229E and MERS-CoV entry, but promote infection by HCoV-OC43, a coronavirus that causes the common cold [33][34][35][36][37][38] . IFITMs, as well as other ISGs, including LY6E and Cholesterol 25-hydrolase (CH25H), impair SARS-CoV-2 replication by blocking the fusion of virions [39][40][41] . Most of the experiments regarding these ISGs have been performed with single-cycle viral pseudotypes.…”
Section: Sars-cov-2 Entry Into Cell Is Initiated By Interactions Betwmentioning
confidence: 99%
“…4H). This enhanced control was likely mediated via the ISG LY6E, which potently restricts SARS-CoV-2 (67,68) and we found to be regulated by ETV7 (Fig. S4B).…”
Section: Suppression Of Etv7 Enhances Ifn-mediated Control Of Influenmentioning
confidence: 72%
“…Additionally, many of the ETV7-regulated ISGs restrict respiratory viruses (42,67,68), and we showed that loss of ETV7 can further enhance the ability of type I IFN to control influenza virus and SARS-CoV-2 replication. Further work is required to understand the complexity of IFN regulation, while therapeutic targeting of factors like ETV7 could lead to the development of a new class of host-directed antivirals that can enhance or tailor ISG responses to specific viruses.…”
mentioning
confidence: 73%